Effects of habitat fragmentation on genetic diversity and population differentiation of Liposcelis bostrychophila badonnel (Psocoptera: Liposcelididae) as revealed by ISSR markers. (July 2016) - Wang, Yinan; Sun, Entao; Wang, Wenlian; Wang, Kang; Wang, Huan; Ge, Mengkai
Abstract: Liposcelis bostrychophila is a globally important stored product pest that is adapted to many habitats and is difficult to control due to insecticide resistance. We evaluated effects of habitat fragmentation on the genetic diversity and differentiation of L. bostrychophila populations. These genetic data were collected in Wuhu city, China using inter-simple sequence repeat (ISSR). A total of 108 discernible DNA fragments were detected, 107 were polymorphic and the percentage of polymorphic bands (PPB) was 99.1%. Shannon's information index ( I ) and Nei's gene diversity ( He ) from four populations were ordered (high to low) as herbstore > flourmill > bedroom > library. Population differentiation ( Gst  = 0.41) was average in these populations. Analysis of molecular variation (AMOVA) showed that variation existed mainly within populations (68.1%). At the same time, gene flow ( Nm  = 0.72) was interpreted to be moderate. Cluster analysis showed a small degree of genetic distance among different isolates and permitted grouping the isolates of L . bostrychophila into three distinct clusters. The study demonstrated clear genetic effects of habitat fragmentation on L . bostrychophila populations. Genetic diversity decreased and genetic differentiation increased between remnant populations when habitats were fragmented. Gene flow is not impeded by habitat fragmentation due to the impact of human activities. These findings are of great use for the prevention and control of this pest. Highlights: Population genetics on Liposcelis bostrychophila populations with habitat fragmentation were first studied by ISSR technology. Habitat fragmentation did obviously influence the population genetics of L. bostrychophila in Wuhu city, China. Genetic diversity on L . bostrychophila decreased with various level can be attributed to human activities in this study. Gene flow on L . bostrychophila isn't impeded by habitat fragmentation in Wuhu area.